DETECTION OF MENDELIAN AND GENOTYPE FREQUENCY OF GROWTH HORMONE GENE IN ONGOLE CROSSBRED CATTLE MATED BY THE ARTIFICIAL INSEMINATION TECHNIQUE - Paputungan, U.; Hakim, L.; Ciptadi, G.; Lapian, H.F.N. (Diponegoro University, 2012)
The objectives of this study were to detect the Mendelian mode inheritance of growth hormone(GH) and to establish genotype frequency of GH gene in Ongole-crossbred cattle mated by the artificialinsemination (AI) technique. Total of 76 blood samples were collected from Ongole-crossbred cows andbulls (G0), and their progenies (G1) at the Tumaratas AI service center in North Sulawesi province,Indonesia. All blood samples were screened for the presence of GH locus using a PCR-RFLP methodinvolving restricted enzyme Msp1 on 1.2 % of agarose gel. Data were analyzed using statistical programfunction in Excel XP. The results showed that GH locus using alleles of Msp1+ and Msp1- enzymerestriction in Ongole-crossbred cows and bulls was inherited to their Ongole-crossbred progeniesfollowing the Mendelian mode inheritance. This Mendelian inheritance generated by AI technique wasnot under genetic equilibrium for the Msp1 genotype frequencies in groups of G0 and G1. The breedingprogram using genotypes of bulls and cows (G0) for generating the genotype of GH Msp1 enzymerestriction by AI technique should be maintained to increase these various allele dispersion rates forbreeding under genetic equilibrium of the Ongole-crossbred cattle population.